Design of a Liquid Hydrogen Export Terminal for Green Hydrogen Transport: a Mediterranean Case Study - Federica Restelli; Laura A. Pellegrini; Saif Z. S. Al Ghafri; Fuyu Jiao; Michael Johns; Eric F. May (Chemical Engineering Transactions)
Implementing hydrogen supply chains using liquid hydrogen (LH2) as a carrier presents significant challenges, among which the design of export terminals due to the boil-off gas (BOG) generation associated with the storage and handling of a cryogenic fluid. This study investigates BOG management at an export terminal through dynamic simulations conducted with Aspen HYSYS® V12.1. The terminal, operating with a LH2 production rate of 44,000 kg/d, is designed to transport green hydrogen from North Africa to Northern Italy over a harbour-to-harbour distance of 2,500 km. The operational cycle, which includes storage tank filling and LH2 carrier loading, spans approximately 10 days, with all generated BOG potentially recoverable through reliquefaction or high-pressure storage. The levelized cost of hydrogen for terminal storage and shipment is estimated at 3.09 €/kg, highlighting the necessity for further research to reduce costs and enable the economic feasibility of LH2 supply chain.